Advanced controls for intelligent buildings : a holistic approach for successful businesses - Goyal, Siddharth (Boca Raton : CRC Press, 2021)
"This book focuses primarily on both technical and business aspects needed to select, design, develop and deploy control application (or product) successfully for multiple components in building systems. Designing and deploying a control application require multiple steps such as sensing, system dynamics modelling, algorithms, and testing. This may involve choosing an appropriate methodology and technique at multiple stages during the development process. Understanding the pros and cons of such techniques, most importantly being aware of practically possible approaches in the entire ecosystem, is critical in choosing the best framework and system application for different parts of building systems. Providing a wide overview of the state-of art in controls and building systems, providing guidance on developing an end-to-end system in relation to business fundamentals (distribution channels, stakeholders, marketing, supply-chain and financial management), the book is ideal for fourth-year control/mechanical/electrical engineering undergraduates, graduate students, and practitioners including business leaders concerned with smart building technology"--
OCLC-licensed vendor bibliographic record.
Keywords: Intelligent buildings; Buildings -- Mechanical equipment -- Automatic control; Building materials industry; COMPUTERS / Computer Engineering; TECHNOLOGY / Electricity; TECHNOLOGY / Electronics / General